Combining modified Graeb score and intracerebral hemorrhage score to predict poor outcome in patients with spontaneous intracerebral hemorrhage undergoing surgical treatment - Wang, Shen; Xu, Xuxu; Yu, Qiang; Hu, Haicheng; Han, Chao; Wang, Ruhai (Frontiers in Neurology, 2022)
Objective: Spontaneous intracerebral hemorrhage (sICH) is a frequently encountered neurosurgical disease. The purpose of this study was to evaluate the relationship between modified Graeb Score (mGS) at admission and clinical outcome of sICH and to investigate whether the combination of ICH score could improve the accuracy of outcome prediction. Methods: We retrospectively reviewed the medical records of 511 patients who underwent surgery for sICH between January 2017 and June 2021. Patient outcome was evaluated by Glasgow Outcome Scale (GOS) score at three months following sICH, where a GOS score of 1-3 was defined as poor prognosis. Univariate and multivariate logistic regression analyses were conducted to determine risk factors for unfavorable clinical outcomes. Receiver operating characteristic (ROC) curve analysis was performed to detect optimal cutoff value of mGS for predicting clinical outcome. An ICH score combining mGS was created, the performance of the ICH score combining mGS was assessed for discriminative ability. Results: Multivariate analysis demonstrated that higher mGS was an independent predictor for poor prognosis (odds ratio 1.207, 95% confidence interval 1.130-1.290, p<0.001). In ROC analysis, optimal cutoff value of mGS to predict clinical outcome at 3 months after sICH was 11 (p<0.001). An increasing ICH-mGS score was associated with increased poor functional outcome. Combining ICH score with mGS resulted in an area under the curve of 0.790, p<0.001. Conclusion: mGS was an independent risk factor for poor outcome and it had an additive predictive value for outcome in patients with sICH. Compared with the ICH score and mGS alone, the ICH score combined with mGS revealed significantly higher discriminative ability for predicting postoperative outcome.